Pendampingan Penggunaan Aplikasi Kolital untuk Penguatan Pendidikan Karakter Siswa Sekolah Dasar - Kartika Yuni Purwanti; Lisa Virdinarti Putra; Iwan Setiawan Wibisono (Ngudi Waluyo Empowerment: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service is aimed at Grade 4 students at SDN Jubelan 01, Sumowono District, Semarang Regency. The problems faced by partners are that students do not understand the importance of literacy, there is no strengthening of character education for students, and teachers have not used literacy-based learning media that are able to strengthen student character education. The methods used are socialization, demonstration and practice of using colital applications, mentoring in the application of colital applications in learning, as well as monitoring and evaluation. The results of this training activity participants have experienced an increase in knowledge and skills with an average of 91.67%, namely understanding of the importance of literacy 85%, student knowledge about strengthening character education 92% and the ability of teachers to manage literacy-based learning to strengthen character education 98 %. Therefore, the results of the mentoring training activity on the use of this collital application can be said to be successful in the very good category. Service programs in the form of strengthening character education need to be pursued, especially in basic education. AbstrakPengabdian ditujukan kepada Siswa Kelas 4 SDN Jubelan 01 Kecamatan Sumowono Kabupaten Semarang. Masalah yang dihadapi mitra adalah siswa belum memahami pentingnya literasi, belum adanya penguatan pendidikan karakter pada siswa, serta guru belum menggunakan media pembelajaran berbasis literasi yang mampu menguatkan pendidikan karakter siswa. Metode yang digunakan adalah sosialisasi, demonstrasi dan praktik penggunaan aplikasi kolital, pendampingan penerapan penggunaan aplikasi kolital dalam pembelajaran, serta monitoring dan evaluasi. Hasil dari pelatihan ini peserta kegiatan telah mengalami peningkatan pengetahuan dan keterampilan dengan rata-rata 91,67%, yaitu pemahaman tentang pentingnya literasi 85%, pengetahuan siswa tentang penguatan pendidikan karakter 92% serta kemampuan guru dalam mengelola pembelajaran berbasis literasi untuk menguatkan pendidikan karakter 98%. Oleh karena itu, hasil kegiatan pelatihan pendampingan penggunaan aplikasi kolital ini dapat dikatakan berhasil dalam kategori sangat baik. Program pengabdian berupa penguatan pendidikan karakter perlu terus diupayakan khususnya di pendidikan dasar.